Evaluating the effectiveness of Human Resource Development best practices on enhancing employee engagement: a study of Manila's University Belt food service sector - De Torres, Pauline Yezha E. Dela Cruz, Julia Mae P. Esteban, Frances Carlyn B. Fuentes, Roan C. Pimentel, Kyla Mae R. 4 0 16; 5
u
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lu ngsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2